Spacecraft Missions to Asteroids - Burch, Tarsha, author 648350 (Delhi, India : University Publication : World Technologies, 2012)
Galileo captures a dynamic eruption at Tvashtar Catena, a chain of volcanic bowls on Jupiter's moon lo Galileo was an unmanned spacecraft sent by NASA to study the planet Jupiter and its moons. Named after the astronomer and Renaissance pioneer Galileo Galilei, it was launched on October 18, 1989 by the Space Shuttle Atlantis on the STS-34 mission. It arrived at Jupiter on December 7, 1995, a little more than six years later, via gravitational assist flybys of Venus and Earth . Despite antenna problems, Galileo conducted the first asteroid flyby near 951 Gaspra, discovered the first asteroid moon Dactyl around asteroid 243 Ida, was the first spacecraft to orbit Jupiter, and launched the first probe into Jupiter's atmosphere.